Knowledge and administration: the change management in a public educational institution, Huánuco, 2023 - Alvarado Rojas, Yowber Andino (2024)
Objective: Analyze the influence of the management of knowledge and administration in the process of organizational change within the Juana Moreno Public Educational Institution, Huánuco, 2023. Materials and methods: The research corresponds to study of approach quantitative, of type prospective, cross-sectional, and explanatory level. The research design was non-experimental correlational. The sample was represented by seventy workers between teachers and administrators. It's used as a technique the survey and as instrument a questionnaire subjected to validation and reliability tests. Results: The Pearson correlation showed a value of 0.76, indicating a strong positive relationship between management of knowledge and administration. The determination index (R² = 0.58) revealed that 58% of the variability in administrative management can be explained by knowledge management. Conclusions: Effective knowledge management is associated with more effective administration in the change process. Knowledge management contributes significantly to decision-making and administrative effectiveness, thus facilitating the implementation of change. However, the remaining 42% of variability suggests that other factors, such as resistance to change and cultural adaptation, also influence change management, and must be considered to ensure a transformation successful of the organization.